Why Motor Competence Matters: Fundamental Movement Skills and Their Role in Promoting Physical Activity and Health in Czech Children Aged 9-10 Years - Kokstejn, Jakub; Grobar, Miroslav; Vampola, Jindrich; Musalek, Martin (Journal of functional morphology and kinesiology, 2025)
Background: Motor competence (MC) plays a critical role in shaping children's physical activity, health-related fitness, and weight status. However, few studies have explored these interrelationships during middle childhood. Objectives: The current study aimed to examine the relationships between MC and physical activity (PA), health-related fitness (HRF), and weight status (WS) in children during middle childhood (9-10 years). Simultaneously, the study aimed to find possible differences in PA, HRF, and WS between children with different levels of MC. Methods: In this cross-sectional study, the TGMD-2 (MC), UNIFITTEST 6-60 (HRF), ActiGraph GT3X (PA), and anthropometry (WS) were administered to 86 children (59 boys, age range of 9-10 years and mean age of 10.1 ± 0.6 years). Results: A significant strong association was observed between MC and HRF (p < 0.01, Cramer's V = 0.42). Significant moderate associations were observed between MC and WS (p < 0.05, Cramer's V = 0.34) and between MC and PA (p < 0.05, Cramer's V = 0.25). Children with high MC proficiency demonstrated significantly higher levels of HRF (p < 0.01; large ES) and PA (p < 0.05; moderate ES) and a healthier WS (p < 0.01; moderate ES) than those with low MC proficiency. Similarly, children with moderate MC proficiency outperformed children with low MC in terms of HRF and WS. Conclusions: The strong associations between MC and key health indicators such as PA, HRF, and WS suggest that movement proficiency in middle childhood should be viewed as a cornerstone of health promotion. Although no causal claims can be made, the results emphasize the practical importance of integrating targeted motor skill development-especially FMSs-into school-based physical education and extracurricular programs. Supporting MC at this age may be a decisive step toward fostering long-term engagement in physical activity and improving children's overall health trajectories.
Keywords: children; motor skills; health-related variables; accelerometry; healthy status